There and back again? Combining habitat suitability modelling and connectivity analyses to assess a potential return of the otter to Switzerland. (19th March 2013) - Cianfrani, C.; Maiorano, L.; Loy, A.; Kranz, A.; Lehmann, A.; Maggini, R.; Guisan, A.
Abstract: After a steady decline in the early 20th century, several terrestrial carnivore species have recently recovered in Western Europe, either through reintroductions or natural recolonization. Because of the large space requirements of these species and potential conflicts with human activities, ensuring their recovery requires the implementation of conservation and management measures that address the environmental, landscape and social dimensions of the problem. Few examples exist of such integrated management. Taking the case of the otter ( Lutra lutra ) in Switzerland, we propose a multi‐step approach that allows to (1) identify areas with potentially suitable habitat, (2) evaluate their connectivity, (3) verify the potentiality of the species recolonization from populations in neighbouring countries. We showed that even though suitable habitat is available for the species and the level of structural connectivity within Switzerland is satisfactory, the level of connectivity with neighbouring populations is crucial to prioritize strategies that favour the species recovery in the field. This research is the first example integrating habitat suitability and connectivity assessment at different scales with other factors in a multi‐step assessment for species recovery.